Relationship of sociodemographic factors on dental caries experience among 11-14-year-old schoolchildren in India - Radhey Shyam; B C Manjunath; Adarsh Kumar; Ridhi Narang; Mamta Ghanghas (Wolters Kluwer Medknow Publications, 2019)
Background: As dynamics of caries is changing, there is a need to understand the impact of sociodemographic factors on dental caries to broaden the horizon of dental caries etiology. Aim: The aim of this study was to assess the relationship of sociodemographic factors on dental caries experience among 11-14-year-old schoolchildren in India. Materials and Methods: A cross-sectional study was carried out among 11-14-year-old schoolchildren in 2015 at Rohtak, India, after approval from the Institution's Ethics Committee. A multi-stage cluster sampling technique was employed for selecting a school randomly from every cluster. Every odd-numbered child from selected class was included in the study through systematic random sampling. Demographic factors were recorded such as education, occupation, income, and socioeconomic status (SES) were assessed using modified Kuppuswamy classification (Oberoi SS 2015). Dental caries was recorded using Caries Assessment Spectrum and Treatment index. Data were analyzed using SPPS 18, Kruskal-Wallis, and Chi-square tests were used with P value fixed at 0.05. Results: The prevalence of dental caries was 28.6% with mean decayed, missing, or filled teeth of 0.60 ± 1.13. Age, gender, position of child, number of siblings, type of family, father's and mother's education, and father's occupation had no significant relationship with dental caries (P > 0.05), whereas mother's occupation, family income, and SES were significantly related to dental caries (P < 0.05). Conclusions: High socioeconomic status of parents had a significant role on increased dental caries experience among children.